Closed-Loop Deep Brain Stimulation to Treat Medication-Refractory Freezing of Gait in Parkinson’s Disease - Molina, Rene; Hass, Chris J.; Cernera, Stephanie; Sowalsky, Kristen; Schmitt, Abigail C.; Roper, Jaimie A.; Martinez-Ramirez, Daniel; Opri, Enrico; Hess, Christopher W.; Eisinger, Robert S.; Foote, Kelly D.; Gunduz, Aysegul; et al. (Frontiers in Human Neuroscience, 2021)
Background: Treating medication refractory freezing of gait (FoG) in Parkinson’s disease (PD) remains challenging despite several trials reporting improvement in motor symptoms using subthalamic nucleus or globus pallidus internus (GPi) deep brain stimulation. Pedunculopontine nucleus (PPN) region DBS has been used for medication refractory FoG with mixed findings. FoG as a paroxysmal phenomenon provides an ideal framework for the possibility of closed-loop DBS (CL-DBS). Methods: In this clinical trial (NCT02318927), five subjects with medication refractory FoG underwent bilateral GPi DBS implantation to address levodopa-responsive PD symptoms with open-loop stimulation. Additionally, PPN DBS leads were implanted for CL-DBS to treat FoG. The primary outcome of the study was a 40% improvement in medication refractory FoG in 60% of subjects at 6 months when “on” PPN CL-DBS. Secondary outcomes included device feasibility to gauge the recruitment potential of this four DBS lead approach for a potentially larger clinical trial. Safety was judged based on adverse events and explantation rate. Findings: The feasibility of this approach was demonstrated as we recruited five subjects with both “on” and “off” medication freezing. The safety for this population of patients receiving four DBS leads was suboptimal and associated with a high explantation rate of 40%. The primary clinical outcome in 3/5 subjects was achieved at 6 months. However, the group analysis of the primary clinical outcome did not reveal benefit. Interpretation: This study of a human PPN CL-DBS trial in medication refractory FoG showed feasibility in recruitment, suboptimal safety, and a heterogeneous clinical effect in FoG outcomes.